Interactions Between Individuals and Sex Rather Than Morphological Traits Drive Intraspecific Dung Removal in Two Dung Beetle Species - Nervo, Beatrice; Laini, Alex; Roggero, Angela; Fabbriciani, Fabrizio; Palestrini, Claudia; Rolando, Antonio (Frontiers in Ecology and Evolution, 2022)
Dung beetle functional ecology has traditionally focused on studying the relation between traits and ecosystem functions in multispecies assemblages, often ignoring the contribution of behavioural interactions and trait variability within species. Here we focus on the factors that affect dung removal at an intraspecific level in two horned dung beetle species with dimorphic males (Onthophagus taurus and O. verticicornis). By setting treatments for each species with single individuals (one female, F; one major male, M; one minor male, m) or with pairs of individuals (MF, mF, MM, mm, FF), we examined the effect on dung removal of morphological traits (head, pronotum, leg, horn), sex, and interactions between individuals. Our results showed that dung removal at an intraspecific level depended more on sex and behavioural interactions than on the underlying morphological traits, whose effects on dung removal were negligible. Single females generally removed more dung than single males, which suggests that females are more effective than males. In both species, pairs with at least one female (MF, mF, FF) showed high dung removal efficiency, but did not perform differently from the sum of single treatments (M+F, m+f, F+F). This suggests an additive effect: males and females (or two females) join their efforts when they are together. The pairs with only males (MM and mm) removed less dung than the sum of the single individuals (M+M and m+m), which indicates a mutual inhibition of males. In both species, male morphs performed similarly as they removed the same amount of dung. Despite our results are limited to two Onthophagus species, we suggest that the intraspecific functional ecology of dung beetles might be more influenced by behavioural interactions and sex rather than by morphological traits.